2019
DOI: 10.1007/s40820-019-0274-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrated System of Solar Cells with Hierarchical NiCo2O4 Battery-Supercapacitor Hybrid Devices for Self-Driving Light-Emitting Diodes

Abstract: Highlights Integration of solar cells, BSHs, and LEDs was developed for energy conversion, storage, and utilization in one system. NiCo 2 O 4 //AC BSHs were charged by a-Si/H solar cells for stably driving LEDs showing high performances. Electronic supplementary material The online version of this article (10.1007/s40820-019-0274-0) contains supplementary material, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 57 publications
1
30
0
Order By: Relevance
“…In general, a practical supercapacitor device tends to self-discharge over time due to thermodynamic effects which include ohmic leakage, side reactions, and overcharging. It was reported that a NiCo 2 O 4 hybrid supercapacitor device exhibited low self-discharge which had a very little voltage drop from 1.6 to 1.594 V after 5 s and unchanged voltage over 24 h. 31 This suggests that the NCO/NCS/NF electrode will also provide such a low selfdischarge property when integrated to a hybrid system. 1.…”
Section: Resultsmentioning
confidence: 98%
“…In general, a practical supercapacitor device tends to self-discharge over time due to thermodynamic effects which include ohmic leakage, side reactions, and overcharging. It was reported that a NiCo 2 O 4 hybrid supercapacitor device exhibited low self-discharge which had a very little voltage drop from 1.6 to 1.594 V after 5 s and unchanged voltage over 24 h. 31 This suggests that the NCO/NCS/NF electrode will also provide such a low selfdischarge property when integrated to a hybrid system. 1.…”
Section: Resultsmentioning
confidence: 98%
“…In general, the energy density of HSCs mainly depends on the electrochemical performances of battery-type electrodes. Thus, considerable efforts have been channeled into designing and exploiting the high-performance electrode materials, especially in the transition metal compounds [17][18][19]. Emerging as a new category of crystalline porous materials with ultrahigh porosity and abundant metal active sites, metal-organic frameworks (MOFs) are assembled by the coordination bond between metal ions and organic ligands, giving the enormous application prospects [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, batteries were used to integrate PV cells, but due to some inadequacies, such as slow charge/discharge capability and short life cycles, supercapacitors are preferred for integration with PV cells. This is attributed to its rapid charging/discharging ability since, first, there is no chemical reaction required, and second, the energy density is reported to be about ten times higher than batteries with the same weight [4,5]. Figure 1 depicts a comparison between batteries, capacitors, supercapacitors and other energy storage devices in terms of specific energy, specific power and the charge/discharge time.…”
Section: Introductionmentioning
confidence: 99%
“…Since the concept of PV cell-supercapacitor integration was introduced in the year 2004, it has sparked interest in many researchers to carry out experimental and simulation work on the fabrication of this device and assess its performance. For instance, a study by [5] integrated hydrogenated amorphous silicon (a-Si/H) solar cells, NiCo 2 O 4 battery supercapacitor hybrids (BSHs) and f light emission diodes (LEDs) into one system. The whole system could work independently with an overall efficiency of 8.1% and the storage efficiency reached 74.24%.…”
Section: Introductionmentioning
confidence: 99%